Role of Zika Virus prM Protein in Viral Pathogenicity and Use in Vaccine Development - Nambala, Peter; Su, Wen-Chi (Frontiers in Microbiology, 2018)
Recent Zika virus (ZIKV) epidemics necessitate the urgent development of effective drugs and vaccines, which can be accelerated by an enhanced understanding of ZIKV biology. One of the ZIKV structural proteins, precursor membrane (prM), plays an important role in the assembly of mature virions through cleavage of prM into M protein. Recent studies have suggested that prM protein might be implicated in the neurovirulence of ZIKV. Most vaccines targeting ZIKV include prM as the immunogen. Here, we review progress in our understanding of ZIKV prM protein and its application in ZIKV vaccine development.